A Remarkable Depth Confusion in Images of the Incomplete Statues of Bruno Catalano. (December 2019) - van Lier, Rob; Ekroll, Vebjørn
Images of Bruno Catalano's sculptures of incomplete bodies give rise to a remarkable depth confusion in which the background is partly pushed to the front. We argue that this confusion is related to what happens in the Kanizsa square, although the effect in the images of Catalano's sculpture appears to be driven by knowledge-based processing.